A Comparative Study of Ropivacaine Alone, Ropivacaine With Tramadol And Ropivacaine With Fentanyl For Caudal Analgesia In Paediatric Infraumbilical Surgery - Shankar, Shilpa; Chakole, Vivek; Singam, Amol (International Journal of Psychosocial Rehabilitation, 2020)
Background/rationale: Caudal epidural analgesia is safe and easy to perform technique of post-operative analgesia in paediatric population undergoing infra umbilical surgery. The major problem encountered in this method of analgesia is the less duration of action of local anaesthetic drug. The addition of an adjuvant drug to the local anaesthetic increases the effectiveness and decreases the dose of the local anaesthetic required. In this study, we use 2 drugs as adjuvants tramadol and fentanyl in an effort to prolong the local anaesthetic drug action. Objectives: Primary objective is to assess the duration of action of sensory blockade/analgesia and duration of time to rescue analgesia. Secondary objectives are to determine the effect on hemodynamic variables (HR,BP,RR,O2 saturation ),duration of motor blockade, postoperative sedation by 4point sedation score, emergence time, and side effects of the drugs. Methodology: This is a hospital based cross-sectional study of 96 patients of age group 1 to 7 years scheduled for infra umbilical surgery. Patients will be randomly allocated into 3 groups (thirty two patients in each group) Group R (n-32) as receiving epidural injection of 1 ml/kg of 0.2% ropivacaine, Group RT (n-32) as receiving epidural injection of 1 ml/kg of 0.2% ropivacaine and 2 mg/kg tramadol, Group RF(n=32) as receiving epidural injection of 1ml/kg of 0.2% ropivacaine and 1 mcg/kg fentanyl. Relevant clinical data will be analysed using appropriate statistical test to find the significant association in clinical factors between the 3 groups. Results: The mean duration of time to rescue analgesia is expected to be longer in the adjuvant groups RT and RF compared to group R. Conclusion: Addition of adjuvant drug tramadol or fentanyl to ropivacaine in caudal epidural block is expected to show significant prolongation of post‑operative analgesia compared to ropivacaine alone without causing significant side effects. Key words: caudal epidural analgesia, paediatric infra umbilical surgery, ropivacaine, tramadol, fentanyl, postoperative analgesia.